PENGARUH LOW COST CARRIER DAN CITRA MEREK TERHADAP KEPUTUSAN CUSTOMER MEMILIH MASKAPAI PENERBANGAN (STUDI KASUS PT INDAH WISATA TOUR) - Yanthy Yosepha, Sri; Oktani Pratiwi, Adisti (Feb Universitas Dirgantara Marsekal Suryadarma, 2018)
This research is purpose to examine the effect of Low Cost Carrier on Customer’s Decision Selecting the Airline at PT Indah Wisata Tour and Travel empirically This research is purpose to examine the effect of Low Cost Carrier and Brand Image on Customer’s Decision Selecting the Airline at PT Indah Wisata Tour and Travel empirically, either partially or simultaneously. This type of research is quantitative descriptive research. Population in this research were 432 respondents and sampling method using non probability sampling with Slovin formula. Based on Slovin formula obtained a sample of 82 size. Hypothesis examination using multiple linear regression analysis, data processing using SPSS version 22.0. Multiple linear regression equation obtained : Y = 3.183 + 0.381 X1 + 0.463 X2 (X1 = Low Cost Carrier, X2 = Brand Image, Y = Customer’s Decision Selecting The Airline). The result of t test indicates that the independent variable Low Cost Carrier (X1) with the result t test 5.120 and Brand Image (X2) with the result t test 6.649 partially has a positive and significant effect on the dependent variable (Y) Customer’s Decision Selecting The Airline. The result of F test 65.248 indicates that both independent variables (X) Low Cost Carrier and Brand Image simultaneously has a positive and significant effect on the dependent variable (Y) Customer’s Decision Selecting the Airline. Contribution of the effect of all independent variables (Low Cost Carrier and Brand Image) on dependent variable (Customer’s Decision Selecting the Airline) is about 61,3%. While the rest is about 38,7% affected by other variables that were not examined. Keywords : Low Cost Carrier, Brand Image and Customer’s Decision Selecting the Airline at PT Indah Wisata Tour and Travel.